2021
DOI: 10.1016/j.euf.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

The “Is mpMRI Enough” or IMRIE Study: A Multicentre Evaluation of Prebiopsy Multiparametric Magnetic Resonance Imaging Compared with Biopsy

Abstract: BackgroundMultiparametric magnetic resonance imaging (mpMRI) is now recommended pre-biopsy in numerous healthcare regions based on the findings of high-quality studies from expert centres. Concern remains about reproducibility of mpMRI to rule-out clinically significant prostate cancer (csPCa) in real-world settings. ObjectiveTo assess the diagnostic performance of mpMRI for csPCa in a real-world setting. Design, Setting, and ParticipantsA multicentre, retrospective cohort study including men referred with a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
1
20
1
Order By: Relevance
“…Stonier et al state that the sensitivity and NPV of transrectal and transperineal biopsy increased to 96.6% and 90.6%, respectively, when a PSA density threshold of 0.15ng/mL/mL was used in nMRI (scores 1–2). 27 Furthermore, Kuhlmann et al identified black race and PSA density as risk factors for the presence of nMRI prostate cancer. 15 Our work indicates that an independent risk factor for csPCa is a smaller prostate gland volume.…”
Section: Discussionmentioning
confidence: 99%
“…Stonier et al state that the sensitivity and NPV of transrectal and transperineal biopsy increased to 96.6% and 90.6%, respectively, when a PSA density threshold of 0.15ng/mL/mL was used in nMRI (scores 1–2). 27 Furthermore, Kuhlmann et al identified black race and PSA density as risk factors for the presence of nMRI prostate cancer. 15 Our work indicates that an independent risk factor for csPCa is a smaller prostate gland volume.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of developing prostate cancer correlates positively with age, PSA level, PSA density, positive family history and palpation findings [1]. It has been shown that consideration of this patientspecific information in addition to the results of mpMRI of the prostate is associated with higher predictive accuracy for the presence of prostate cancer, lower number of negative biopsies, higher staging accuracy, and higher predictive accuracy for upgrading biopsy results [2][3][4][5][6].…”
Section: Case History Datamentioning
confidence: 99%
“…These advantages minimize the harms of unnecessary biopsies, over-diagnoses, and over-treatments [9]. These benefits are related to the consistent high negative predictive value (NPV) and sensitivity of MRI for PCa detection [10,11] that enable the reliable "ruling-out" of csPCa without needing biopsies [7,12]. A recent meta-analysis of 36 studies including more than 5000 biopsy-naïve men had an NPV of 91% (95% CI 88-96%), meaning that 1 in 10 men with International Society of Uropathology (ISUP) Gleason Grade (GG) ≥ 2 remained undiagnosed [10].…”
mentioning
confidence: 99%
“…We must remember that most of the prospective level 1 evidence studies used for guideline development were performed in high-volume expert centers [2,5,6]. However, "real-world" studies show similar NPVs, despite heterogeneities in disease prevalence, MRI scanners, and expertise of radiologists, urologists, and pathologists [1,3,8,10,11]. These concordant data reenforced the guideline recommendations to use MRI-negative results for avoiding prostate biopsies, with appropriate clinical caveats and safety-nets protocols [13][14][15].…”
mentioning
confidence: 99%
See 1 more Smart Citation